PENGARUH KEPUASAN KERJA, KOMPENSASI DAN PENGEMBANGAN KARIR TERHADAP TURNOVER INTENTION KARYAWAN BANK SYARIAH MANDIRI CABANG PADANG - Adi Bibowo; Erni Masdupi (Program Studi Magister Manajemen, 2015)
The research is proposed to determine the influence of job satisfaction, compensation and career development to turnover intention of BSM branch Padang’s employee. The population in this research were organic employee of BSM branch Padang. The number 84 organic employee as research sample is determined by using Slovin formula and elected by using cluster random sampling techniqe. Primary and secondary data are used in this research. Analysis data technique is using path analysis dan hypotesis test by using t test with SPSS version 20 is used to analyzed the data. The result of this research shows that the compensation and career development are positively and significantly affect job satisfaction. Furthermore, compensation, career development and job satisfaction all together have a significant influence to turnover intention but individually only job satisfaction that have a significant and negative effect to turnover intention. Keywords : Job satisfaction, Compensation, Career development, Turnover intention